Persepsi Keadilan dan Ketidakpastian Lingkungan Sebagai Pemoderasi Pengaruh Partisipasi Penganggaran Pada Senjangan Anggaran - T. Marjana, Ayunia Gina; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 22 No 2 (2018), 2018)
This study aims to test and provide empirical evidence of the role of fairness perception that’s proxied with procedural fairness and distributive fairness, and environmental uncertainty in influencing the relationship of budgetary participation in budgetary slack. This research was conducted on 28 star hotels in Badung regency. The number of respondents used was 77 heads of departments selected using purposive sampling with respondent criteria head of accounting department, head of front office department, and head of food & beverages department who participated in budget and have occupied his position at least one year. Methods of data collection were conducted by survey method using questionnaire. Data analysis technique used is Moderated Regression Analysis (MRA). The final results of the study suggest that procedural fairness and distributive fairness weaken the influence of budgetary participation on budgetary slack. While environmental uncertainty strengthens the influence of budget participation on budget slack. Keywords: Participative budgeting, procedural fairness, distributive fairness, environmental uncertainty, budgetary slack